Internet of things based visualisation of effect of air pollution on the lungs using HEPA filters air cleaner - Katushabe, Calorine; Santhi, Kumaran; Masabo, Emmanuel (Heliyon, 2023)
The impact of air quality on human health and the environment is very significant, with poor air quality being responsible for numerous deaths and environmental damage worldwide. Whereas a number of studies have been done to monitor the quality of air with help of emerging technologies, little has been done to visualize its effect on health particularly on the lungs. The study explores an approach that combines Internet of Things (IoT) technology with High Efficiency Particulate Air (HEPA) filters air cleaner to monitor and visualize the effects of air pollution on lung health, highlighting the significant damage that poor air quality causes particularly on the lungs graphically. To achieve this, a 3D display of the lungs is modelled using HEPA filters, which changes colour based on the air pollutant concentrations detected by IoT based sensors. The collected air quality data is then transmitted to Thingspeak, a visualization platform for further analysis. It is observed that the colour of the 3D lung display changed to black over time as air pollutant concentrations increased which in our study is an indicator of unhealthy lung. The study presents an innovative approach to visualize the effects of air pollution on lung health using IoT and HEPA filters air cleaner, which could have significant implications for public health policies aimed at mitigating the harmful effects of air pollution, particularly on lung health.